Hubungan Mutu Pelayanan Terhadap Kepuasan Pengguna Platform Halodoc Di Jabodetabek Tahun 2021 - Afifa Nur Chabibah; Agustin Kusumayati (NERSMID : Jurnal Keperawatan dan Kebidanan, 2021)
The increasing number of COVID-19 cases has caused the government to issue an appeal letter not to practice routine except for emergencies in health care facilities and advise the public to use online health services or telehealth. This has led to a 2 times increase in application downloads, 18 million monthly active users, 10 times paid doctor consultation transactions, 6 times health store services and 3 times the Make Appointment service on the Halodoc platform. The increase must pay attention to quality and customer satisfaction. The purpose of this study was to determine the relationship between service quality and user satisfaction on the Halodoc platform in Jabodetabek in 2021. The research method was quantitative analytic with an observational approach and a cross sectional research design. Respondents were 192 users of the Halodoc platform and were collected through an online questionnaire using a purposive sampling method, namely accidental sampling. The results showed that the majority of Halodoc platform users are teenagers aged between 17-25 (39.6%), female (70.8%), highly educated (70.8%) and high income (58.9%) with self-employed jobs (43.8%) and the majority live in Jakarta (43.2%) with a frequency of using the Halodoc platform 1-2 times (51.6%). There is a relationship between service quality and satisfaction indicating a significant and positive relationship (p value = 0.000) where a good service quality on the Halodoc platform can increase customer satisfaction by 11.6 times greater than the poor service quality. Suggestions that can be given are to increase personalization and assurance on the Halodoc platform according to the characteristics of each respondent so as to increase customer satisfaction.